Characteristics of an elderly hypertensive population assisted at a family health unit - Romero, Adriana Diógenes; Silva, Maria Josefina da; Silva, Ana Roberta Vilarouca da; Freitas, Roberto Wagner Júnior Freire de; Damasceno, Marta Maria Coelho (Rev Rene, 2010)
This investigation aimed at learning about the characteristics of an elderly population with arterial hypertension. It is a transversal study that involved 57 individuals and was performed at a Family Health Unit in the city of Fortaleza-CE. The collection of data occurred from April to May, 2007 by applying a questionnaire on age, gender, income, family history of arterial hypertension, daily health habits and information on medical treatment. Results highlighted that 54.5% were between 60-69 years of age; 95% had a minimum-wage income; 75.5% were women; 49% were sedentary; 52.6% had three meals a day; 50.8% reported arterial hypertension cases in the family; 80.7% knew about the disease, and 96.5% followed the medical treatment. It was concluded that the old aged studied needed guidance with regard to watching the group of aspects concerning arterial hypertension and, thus, prevent complications resulting from this disease.